2007
DOI: 10.1111/j.1365-2516.2007.01501.x
|View full text |Cite
|
Sign up to set email alerts
|

Identifying and overcoming barriers to prophylaxis in the management of haemophilia

Abstract: Haemophilia is often characterized by acute haemarthrosis and synovitis arising from spontaneous bleeding episodes, particularly in the muscles and joints of the elbows, knees and ankles. Current treatment for patients with severe haemophilia involves coagulation factor concentrate (CFC) replacement therapy given on demand at the time of bleeding or through long-term prophylaxis aimed at preventing future bleeds and joint disease. Although prophylaxis has many advantages over on-demand therapy (particularly if… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
81
1
5

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 75 publications
(87 citation statements)
references
References 37 publications
0
81
1
5
Order By: Relevance
“…These results were backed by a prospective 10 year Italian trial (ESPRIT), which enrolled 40 patients younger than 7 years of age with negative clinical and radiological scores for joint damage; patients were randomized to be treated with rFVIII 25 IU Kg three times a week or on-demand (25 IU Kg) until complete bleed control, results indicated that prophylaxis is associated with significantly fewer breakthrough bleeds than on-demand treatment (0.24 vs. 1.30 bleeds per month, respectively; P \ 0.001) [18][19][20]. A retrospective cohort analysis involving 156 Norwegian and Swedish patients suggested that patients who received prophylaxis required fewer total invasive procedures than those who received on-demand treatment [21]. Less number of bleeding episodes, and lifethreatening haemorrhages under prophylaxis, should be associated with a much better joint status and a better quality of life.…”
Section: Summary Of Findings On Treatmentmentioning
confidence: 99%
See 3 more Smart Citations
“…These results were backed by a prospective 10 year Italian trial (ESPRIT), which enrolled 40 patients younger than 7 years of age with negative clinical and radiological scores for joint damage; patients were randomized to be treated with rFVIII 25 IU Kg three times a week or on-demand (25 IU Kg) until complete bleed control, results indicated that prophylaxis is associated with significantly fewer breakthrough bleeds than on-demand treatment (0.24 vs. 1.30 bleeds per month, respectively; P \ 0.001) [18][19][20]. A retrospective cohort analysis involving 156 Norwegian and Swedish patients suggested that patients who received prophylaxis required fewer total invasive procedures than those who received on-demand treatment [21]. Less number of bleeding episodes, and lifethreatening haemorrhages under prophylaxis, should be associated with a much better joint status and a better quality of life.…”
Section: Summary Of Findings On Treatmentmentioning
confidence: 99%
“…It is intended to reduce the risk of other serious haemorrhage, such as intracranial bleeds [29]. In a study of 21 patients receiving secondary prophylaxis at three different ages (1-2, 3-6 and[6 years), Kreuz et al found that although the number of joint bleeds decreased significantly during prophylaxis in the two older groups, radiologic and orthopaedic scores still deteriorated for those who reported more than five joint bleeds before the initiation of prophylaxis, suggesting that once joint damage had started, further joint deterioration could not be prevented by the initiation of prophylactic therapy [21], even though secondary prophylaxis cannot reverse the changes of chronic arthropathy, it may be beneficial by reducing frequency of bleeding, hospital admissions and lost days from school or work, and by decreasing damage progression. Patients treated with secondary prophylaxis had a decreased number of joint bleeding episodes at the expense of higher clotting factor concentrate consumption [4].…”
Section: Summary Of Findings On Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the use of CVLs has been linked to a risk of infection of 0.2-1 per 1,000 days, and possible thrombosis. 7 Although the occurrence of thrombosis has historically been underestimated, it is now understood that it can occur in 15-53% of patients with CVLs, even with a diagnosis of haemophilia.…”
Section: Potential Obstacles In Prophylaxismentioning
confidence: 99%